Produção e reprodução de bovinos de corte - Silva, Silvio Oliveira da (Universidade Federal do Tocantins, 2022)
The mandatory supervised curricular internship was conducted under the supervision of veterinarian Yan Oliveira Lacerda, a liberal professional, who provides services in the areas of animal reproduction and production, and under the guidance of professor. Dra. Fabiana Cordeiro Rosa. The internship took place from January 19 to April 1, 2021, with a workload of 424 hours. Activities were carried out in the areas of animal production and reproduction in properties located in the northern region of the state of Tocantins and southeast of the state of Pará. The main activities developed were, gynecological examination, fixed-time artificial insemination (IATF), diagnosis of pregnancy by transrectal palpation and ultrasound, maternity management, training of rural employees and phenotypic selection of matrices. The mandatory supervised curricular internship is essential for graduation in the course in veterinary medicine, allowing the improvement of the techniques acquired during their academic training, experiencing in practice what is the professional reality, preparing the student to work in the job market. Very important experience for the professional future.